2014
DOI: 10.1038/jp.2014.206
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of pain during application of nasal-continuous positive airway pressure and heated, humidified high-flow nasal cannulae in preterm infants

Abstract: The application of HHHFNC in preterm infants is associated with less pain compared with nCPAP, as it is associated with less PIPP scores and lower salivary-cortisol concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 38 publications
0
49
0
Order By: Relevance
“…Low-flow nasal cannula is commonly used in pediatrics. A comparison of HFNC with nasal CPAP (nCPAP) in preterm infants showed lower pain scores and less-physiologic stress response [17]. Attempts to use higher flows increase the risk of desiccation and mucosal compromise.…”
Section: Comparison With Other Modes Of Oxygen Delivery and Respiratomentioning
confidence: 99%
“…Low-flow nasal cannula is commonly used in pediatrics. A comparison of HFNC with nasal CPAP (nCPAP) in preterm infants showed lower pain scores and less-physiologic stress response [17]. Attempts to use higher flows increase the risk of desiccation and mucosal compromise.…”
Section: Comparison With Other Modes Of Oxygen Delivery and Respiratomentioning
confidence: 99%
“…91,93,95 Two additional studies did not assess respiratory failure, but compared pain and/or discomfort scores; an observational cross-sectional study in 60 preterm infants revealed that the application of HFNC was associated with less pain compared with nCPAP, 97 whereas a randomized crossover study in 20 preterm infants revealed no differences during treatment. 92 Collins et al 90 randomly assigned 132 mechanically ventilated preterm infants <32 weeks' gestational age to HFNC at 8 L/minute or nCPAP at either 7 or 8 cm H 2 O, depending on supplemental oxygen requirement.…”
Section: Hfnc Versus Cpap For Noninvasive Respiratory Support Of Pretmentioning
confidence: 99%
“…This approach has several reported advantages over CPAP, including reduced rates of nasal trauma [7][8][9] and reduced infant pain scores. 10 Surveys show that it is preferred by parents 11 and nursing staff. 12 In a previous randomized trial comparing high-flow therapy with CPAP as respiratory support after extubation in infants born at a gestational age of less than 32 weeks, we found that high-flow therapy was noninferior to CPAP in preventing treatment failure.…”
mentioning
confidence: 99%